Semantic enrichment of a web legal information retrieval system - Saias, José (2012)
A methodology to semi-automatically transform a traditional web IR system into a semantic aware one is proposed. The methodology is composed by three major steps: construction of an appropriate semantic ontology; text enrichment with semantic information; and construction of the inference engine. In order to create an adequate ontology, natural language processing techniques are applied, such as, partial parsers and lexical information (WordNet). Documents are enriched with semantic information using the output of the partial parsers and the obtained ontology. Finally, an infer- ence engine based on a declarative rogramming language – Prolog – is used as the basis for the reasoning process.